Rozwiąż nierówności .
a) x+7<15
b)-2x+3>9
c)4x-11<10
d)5x+7>-23
e)10x+8≥6x+16
f)6-2x≤5x+8
g)3x-3+2x≥-4+2x
h)5x+15≤30-2x
i)2(x-1)+3x>3(x+2)+6
j)x-4-3(x-10)≤x+6
k)6x-2(x+1)<12
l)3(x-2)+4(x-2)>8
m)2(x+2)+(2x-3)≤x-10
n)x(x-3)-(x-2x-5)≥2x+4

1

Odpowiedzi

2010-04-15T16:23:30+02:00
A)x+7<15
x<15-7
x<8
b)-2x+3>9
-2x>9-3
-2x>6
x<-3
c)4x-11<10
4x<10+11
4x<22
x<5,5
d)5x+7>-23
5x>-23 -7
5x>-30
x>-6
e)10x+8≥6x+16
10x-6x≥16-8
4x≥8
x≥2
f)6-2x≤5x+8
-2x-5x≤8-6
-7x≤2
x≥- 2/7
g)3x-3+2x≥-4+2x
3x+2x-2x≥-4 +3
3x≥-1
x≥ -1/3
h)5x+15≤30-2x
5x+2x≤30-15
7x≤15
x≤2 1/7
i)2(x-1)+3x>3(x+2)+6
2x-2+3x>3x+6+6
2x+3x-3x>6+6+2
2x>14
x>7
j)x-4-3(x-10)≤x+6
x-4-3x+30≤x+6
x-3x-x≤6+4-30
-3x≤-20
x≥6 2/3
k)6x-2(x+1)<12
6x-2x-2<12
6x-2x<12-2
4x<10
x<2 2/4
l)3(x-2)+4(x-2)>8
3x-6+4x-8>8
7x>8+6-8
7x>6
x>6/7
m)2(x+2)+(2x-3)≤x-10
2x+4+2x-3≤x-10
2x+2x-x≤-10-4+3
3x≤-11
x≤-3 2/3
n)x(x-3)-(x-2x-5)≥2x+4
x²-3x-x+2x+5≥2x+4
x²-3x-x+2x-2x≥4-5
x²-4x≥-1